Report of the expert meeting on assessing the impact of public-private partnerships on trade and development in developing countries (UN New YorkUS, 2013)
Discusses key issues in the public-private partnership (PPP) arrangements. Reviews the key drivers and most effective institutional set-up for PPPs and the creation of the environment to enable SMEs to tap opportunities created by global value chains. Measures the impact of PPPs.
Keywords: PUBLIC SECTOR